Boosted Interfacial Polarization from Multishell TiO2@Fe3O4@PPy Heterojunction for Enhanced Microwave Absorption. Issue 36 (16th July 2019) - Ding, Jingjun; Wang, Lei; Zhao, Yunhao; Xing, Linshen; Yu, Xuefeng; Chen, Guanyu; Zhang, Jie; Che, Renchao
Abstract: Core@shell structures have been attracting extensive attention to boost microwave absorption (MA) performance due to the unique interfacial polarization. However, it still remains a challenge to synthesize sophisticated 1D semiconductor‐based materials with excellent MA competence. Herein, a hierarchical cable‐like TiO2 @Fe3 O4 @PPy is fabricated by a sequential process of solvothermal treatment and polymerization. The complex permittivity of ternary composites can be optimized by tunable PPy coating thickness to improve the loss ability. The maximum reflection loss can reach −61.8 dB with a thickness of 3.2 mm while the efficient absorption bandwidth can achieve over 6.0 GHz, which involves the X and Ku band at only a 2.2 mm thickness. Importantly, the heterojunction contacts constructed by PPy–Fe3 O4 and Fe3 O4 –TiO2 contribute to the enhanced polarization loss. Besides, the configuration of magnetic Fe3 O4 sandwiched between dielectric TiO2 and PPy facilitates the magnetic stray field to radiate into the TiO2 core and out of the PPy shell, which significantly promotes magnetic–dielectric synergy. Electron holography validates the distinct charge distribution and magnetic coupling. The new findings might shed light on novel structures for functional core@shell composites and the design of semiconductor‐based materials for microwave absorption. Abstract : Hierarchical core@shell TiO2 @Fe3 O4 @PPy is well‐optimized to exhibit tunable broadband microwave absorption owing to the improved dielectricity and magnetism. The heterojunction contacts constructed by semiconductors contribute to boosted interfacial polarization while the controllable PPy thickness is conducive to regulation of the conductivity. This engineered strategy provides inspirations for functional core@shell materials in various applications.